2002
DOI: 10.1046/j.1460-9592.2002.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation of “Typical” Atrial Flutter in a Patient with Kartagener's Syndrome

Abstract: Kartagener's syndrome and radiofrequency catheter ablation for the treatment of atrial flutter have been well described in separate reports. This case report includes both in describing a patient with Kartagener's syndrome who had medically refractory atrial flutter that was successfully treated with radiofrequency catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Congenital heart disease is relatively low among these individuals and is estimated to be about 3% 1 . There have been six case reports 2–7 of radiofrequency catheter ablation of supraventricular arrhythmias in patients with dextrocardia, complete situs inversus, and no other cardiac abnormalities. In such cases, radiofrequency ablation could be successfully performed with no particular difficulties if the operator could keep the patient's dextrocardia in mind (e.g., right instead of left, clockwise instead of counter‐clockwise).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital heart disease is relatively low among these individuals and is estimated to be about 3% 1 . There have been six case reports 2–7 of radiofrequency catheter ablation of supraventricular arrhythmias in patients with dextrocardia, complete situs inversus, and no other cardiac abnormalities. In such cases, radiofrequency ablation could be successfully performed with no particular difficulties if the operator could keep the patient's dextrocardia in mind (e.g., right instead of left, clockwise instead of counter‐clockwise).…”
Section: Discussionmentioning
confidence: 99%
“…Complete situs inversus is a rare anomaly with a prevalence of 0.02% in the general population 1 . There have been a few reports of radiofrequency catheter ablation of supraventricular tachyarrhythmias in dextrocardia with complete situs inversus and no other anomalies 2–8 . Although an anomalous inferior vena cava (IVC) occurs in 8–18% of the patients with dextrocardia, 9,10 radiofrequency catheter ablation of the arrhythmias in such cases has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Abe et al 3 suggested the use of biplane fluoroscopy as a valuable tool for catheter positioning, although not widely available. Herreros et al 6 used a regular monoplane system successfully, whereas other authors reported successful ablation procedures of flutter 7 or atrial tachycardia 4–5 in patients with mirror‐image dextrocardia. A regular procedure used in most cases was the 12‐lead ECG “correction” of the chest as well as the limb leads.…”
Section: Discussionmentioning
confidence: 99%
“…Mirror image dextrocardia, whether as an isolated entity or associated with Kartagener's syndrome, 1 has been the subject of sporadic reports in arrhythmia specialized journals 2–7 . The particular interest in these cases arises from difficulties in analyzing inverted cardiac signals as well as manipulating and maneuvering catheters in a mirror image environment.…”
Section: Introductionmentioning
confidence: 99%
“…There has been limited experience with radiofrequency catheter ablation in patients with dextrocardia. Successful catheter ablation of atrial tachycardia, atrial flutter, and an accessory pathway has been reported in patients with dextrocardia 1–6 . AV nodal reentrant tachycardia was also reported in a patient with dextrocardia who had single aortic coronary ostium, however, ablation was not attempted 7 .…”
Section: Case Reportmentioning
confidence: 99%